ANALISIS SISTEM PEMBANGKIT LISTRIK TENAGA HYBRID (SOLAR CELL DAN WIND TURBINE) UNTUK KELISTRIKAN RUMAH TINGGAL - -, Rohmaniyyah; Anisah, Siti (Politeknik Harapan Bersama Tegal, 2024)
Hybrid Power Plant (PLTH) is a power plant connected from various types of renewable energy sources or with non-renewable energy sources. The limited conventional energy sources are the reasons behind the growing use of renewable energy in Indonesia. One of the potential energies to be developed in Indonesia is solar energy and wind energy. This study aims to design a small-scale PLTH, then analyze the output power generated when the hybrid generator operates using batteries as an indicator. The control process occurs by using voltage display as a means to determine the voltage on each genset and battery. The first method used is a study of the potential of these two energies. Then calculate the capacity needed for each component. Next is to prepare the design of the generator whose capacity has been calculated to become a hybrid generator. The final step is to implement the genset design to be applied to small-scale household loads of 40 Watts including 2 lights and 1 fan. Based on the design results obtained from the solar cell, the module size is 40 Wp, the fill factor is 0.73, and the efficiency is 13%, while the wind turbine design produces power of 1.169 Watts with a wind speed of 3.5 m/s and the highest efficiency reaching 64%. Then the solar charge controller capacity is 2.32 A, the inverter capacity is 50 Watts, and the total battery energy is 3.33 Ah. Battery charging takes 6.6 hours in clear weather and 8.3 hours in cloudy weather, reaching 20%-100% of its capacity.